2020
DOI: 10.9734/ijpss/2020/v32i230244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indigenous Rhizobia Strains Associated to Soybean [Glycine max (L.) Merrill] in Benin

Abstract: Legumes such as soybean establish symbiotic relation with nitrogen fixing bacteria such as Rhizobia. Nitrogen fixation via legume-rhizobium symbiosis is the most important source of Nitrogen in agro-ecosystems. But environmental stresses are important limiting factors for this process. Hence, the aim of this study is to evaluate the physiological characteristics and Plant Growth Promoting (PGP) properties of soybean rhizobia. A total of 28 Rhizobia strains obtained from soybean root nodules collected in from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Ohyama et al [32] reported that soybean yield could increase up to 4.6 t•ha −1 under prime environmental (climatic and soil) conditions. However, the USA and Japan have reported greater potential soybean yields of 10 and 8 t•ha −1 , respectively [32,33]. Hence, soybean productivity potential could be maximized than we have thought if proper soil and crop management practices are used [34].…”
Section: General Information About Soybean Productionmentioning
confidence: 86%
“…Ohyama et al [32] reported that soybean yield could increase up to 4.6 t•ha −1 under prime environmental (climatic and soil) conditions. However, the USA and Japan have reported greater potential soybean yields of 10 and 8 t•ha −1 , respectively [32,33]. Hence, soybean productivity potential could be maximized than we have thought if proper soil and crop management practices are used [34].…”
Section: General Information About Soybean Productionmentioning
confidence: 86%
“…Another notable indirect mechanism involves the production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase that assists in alleviating the effects of stress (e.g., drought, salinity, heat, cold, and exposure to heavy metals) on plant growth, as it limits the formation of ethylene produced in response to stress (i.e., ACC, the immediate precursor of ethylene is degraded by ACC deaminase to alpha-ketobutyrate and ammonia) [31,33]. These abilities have been witnessed among Mesorhizobium whereby M. ciceri, M. loti, M. tianshanense, M. huakuii, M. mediterraneum, M. temperatum, and M. amorphae are capable of producing IAA to varying levels [34], and solubilize phosphate [33,35,36]. They are, however, unable to produce siderophores [27]; although, certain strains produce siderophores when exposed to particular pesticides and fungicides [37,38].…”
Section: Introductionmentioning
confidence: 99%